2021
DOI: 10.1093/femsec/fiab043
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacteria formation and influencing factors

Abstract: The gut microbiota plays an important role in human health. In modern life, with the improvement of living conditions, the intake of high-sugar and high-fat diets as well as the large-scale use of antibacterial drugs have an extensive impact on the gut microbiota, even leading to gut microbiota-orchestrating disorders. This review discusses the effects of various factors, including geographic location, age, diet, antibacterial drugs, psychological situation and exercise on gut bacteria, which helps us profound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Certainly, levels of gut microbiota are susceptible to many factors, such as age, gender, diet, geographical location, exercise, drug usage, metabolism, and surgery ( Yang et al, 2021 ). Especially, ketogenic diet can control seizure attack.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, levels of gut microbiota are susceptible to many factors, such as age, gender, diet, geographical location, exercise, drug usage, metabolism, and surgery ( Yang et al, 2021 ). Especially, ketogenic diet can control seizure attack.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the gastrointestinal tract is one of the critical immune organs of the body, which also helps resist the invasion of exogenous pathogenic factors and maintains the homeostasis of the intestinal environment [ 40 ]. It is normal for the gut microbiota, the host, and the external environment to establish a dynamic equilibrium, and the type and quantity of the gut microbiota are relatively stable [ 41 ]. However, AFB1 exposure disrupts the gut microbiota [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that there was a significant difference in the mean age between PA patients and primary hypertension patients. Several studies have revealed that age is a factor influencing the gut microbiota (41)(42)(43)(44). As people age, key changes in gut microbiota include compositional instability, reduced overall diversity, and an increase in proinflammatory opportunistic pathogens.…”
Section: Discussionmentioning
confidence: 99%